Complementary characterization method of 3D arsenic doping by using medium energy ion scattering. (22nd January 2021) - Woguia, L Penlap; Pierre, F; Sanchez, D F; Marmitt, G G; Saghi, Z; Jalabert, D
Abstract: We report on a new characterization method of 3D—doping performed by arsenic implantation into FinFET—like nanostructures by using Medium Energy Ion Scattering. Because of its good depth resolution (0.25 nm) at the surface, it is one of techniques of choice suitable to analyse the ultra-shallow doping of thin crystal films. However, with the constraints related to the nanostructures' geometry and the low lateral resolution of the MEIS beam (0.5 × 1 mm 2 ), we developed an adequate protocol allowing their analysis with this technique. It encompasses three different geometries to account for the MEIS spectra of the arsenic implanted in each part of the nanostructures. The originality of the protocol is that, according to the chosen analysis geometry, the overall spectrum of arsenic is not the same because the contributions of each part of the patterns to its formation are different. By using two of them, we observed double peaks of arsenic. Thanks to 3D deconvolutions performed with PowerMEIS simulations, we were able to identify the contribution of the tops, sidewalls and bottoms in their formation. Thus, by separating the spectrum of the dopants implanted in the Fins (tops + sidewalls) from that of the bottoms, we were able to characterize the 3D doping conformity in the patterns. Two different implantation methods with the associated local doses computed in each single part were investigated. We found that the distribution of the dopants implanted by using the conventional implanter method is very different from that of plasma doping.